2006
DOI: 10.1186/1471-244x-6-56
|View full text |Cite
|
Sign up to set email alerts
|

Regional gray matter volumetric changes in autism associated with social and repetitive behavior symptoms

Abstract: Background: Although differences in brain anatomy in autism have been difficult to replicate using manual tracing methods, automated whole brain analyses have begun to find consistent differences in regions of the brain associated with the social cognitive processes that are often impaired in autism. We attempted to replicate these whole brain studies and to correlate regional volume changes with several autism symptom measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
285
4
6

Year Published

2010
2010
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 323 publications
(334 citation statements)
references
References 89 publications
(76 reference statements)
34
285
4
6
Order By: Relevance
“…The present correlation is in line with recent findings: (i) posterior superior temporal volume can be linked to loneliness and the ability to recognize social signals (i.e., eye gaze; Kanai et al 2012); and (ii) enhanced social ability (i.e., imitation and perspective talking) can be obtained by stimulating right temporoparietal junction via transcranial direct current stimulation (Santiesteban et al 2012). Our findings thus nicely complement previous studies relating brain structure abnormalities in ASD to behavioral measures (Rojas et al, 2006;Dziobek et al, 2010), and show similar relations in the domain of motion perception.…”
Section: Regional Gray Matter Abnormalities and Their Correlation Witsupporting
confidence: 90%
See 1 more Smart Citation
“…The present correlation is in line with recent findings: (i) posterior superior temporal volume can be linked to loneliness and the ability to recognize social signals (i.e., eye gaze; Kanai et al 2012); and (ii) enhanced social ability (i.e., imitation and perspective talking) can be obtained by stimulating right temporoparietal junction via transcranial direct current stimulation (Santiesteban et al 2012). Our findings thus nicely complement previous studies relating brain structure abnormalities in ASD to behavioral measures (Rojas et al, 2006;Dziobek et al, 2010), and show similar relations in the domain of motion perception.…”
Section: Regional Gray Matter Abnormalities and Their Correlation Witsupporting
confidence: 90%
“…The question arises whether the variation of social behavior deficits and of other behavioral aspects of ASD can be related to the morphology of brain regions associated with the disorder. One of the few studies that have addressed such questions directly so far has found an association between social and communication deficits in ASD with caudate, cerebellar, and precuneus volumes, as well as with frontal and temporal lobe regional volumes (Rojas et al, 2006). Another study found abnormalities in the amygdala-fusiform system in ASD, including and an increase in cortical thickness in a fusiform region of interest in ASD compared to controls, together with a negative correlation between cortical thickness in this region and facial emotion recognition in ASD (Dziobek et al 2010).…”
mentioning
confidence: 99%
“…11,12 These areas also have been found affected in our study. Higher than normal density, not observed by us, has been reported in inferior frontal cortex 10,13 and cerebellum. 3,8,14 Other investigations identified areas of higher or lower GM density that were unaffected in our patients, such as the amygdala, 8 cingulate gyrus, 8,11 fusiform gyrus, 10,14 and thalamus.…”
Section: Discussionmentioning
confidence: 61%
“…Redcay et al have reported that impaired social communication and language result from the abnormalities in the Broca and Wernicke areas [62]. There is also evidences that frontotemporal regions and amygdala have been associated with abnormalities in socioemotional processing [30,34]. It has been suggested that orbitofrontal cortex and caudate nucleus may be linked to repetitive and stereotyped behaviours [63].…”
Section: Discussionmentioning
confidence: 99%
“…Also, abnormally concentrated gray matter in the right fusiform gyrus of autisitc patients is revealed in a VBM study [34].…”
Section: Fusiform Areamentioning
confidence: 99%